Use of dental services among adults from a birth cohort in the South region of Brazil - Rafaela do Carmo Borges; Mariana Silveira Echeverria; Sarah Arangurem Karam; Bernardo Lessa Horta; Flávio Fernando Demarco (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE Measure the prevalence of use of dental services in the previous year and associated factors among 31-year-old adults from a birth cohort of 1982. METHODS This is a cross-sectional study that analyzed a birth cohort of 1982 from the city of Pelotas. In 1997, a systematic sample of 27% of the city's census sectors was defined and all households in these sectors were visited, where 1,076 15-year-old adolescents were interviewed. For the oral health studies, 900 of these individuals were randomly selected and followed up at 24 and 31 years of age. The study used data collected from 523 individuals in 2013 (at 31 years old). The outcome was visit to the dentist (use of dental services) in the previous year. Demographic factors (sex), socioeconomic factors (income, education), and oral health factors (reason and type of service, self-perception of oral health, dental pain and caries experience - DMFT) were used as independent variables. Prevalence ratios were estimated using Poisson regression. RESULTS The prevalence of use of dental services in the previous year was 55.3% (95%CI: 51.0-59.5%). In the adjusted analysis, the reason and type of service, self-perception of oral health, and DMFT were associated with the outcome. A stronger association was found with use of dental services in individuals who visited for prevention and used the private service, who were satisfied with their oral health, and who had more caries experiences. CONCLUSION 55.3% of the cohort sample used dental services in the previous year. Individuals who visited the dentist of private service for preventive reasons, who were very satisfied with their oral health, used these services in a higher proportion. In addition, a higher DMFT index also led to higher use of services.